The Degree of Compliance Based on Excise Duties in Romania Between 2002 and 2015 - Todor, Silvia Paula; Ghiur, Rodica; Brezeanu, Petre; Dumiter, Florin; Boiță, Marius (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2017)
The fiscal policy is an instrument that collects resources for the state budget necessary to perform state functions; stabilize the economy; regulation of the economy and recovery growth. The most important instruments are taxes and taxpayers. Since 1989, with the transition to a market economy, a special tax policy has been known by excise taxes. Analyzing the case of Romania and the evolution of excise duties (hereinafter ED) conformity we created some regressions that illustrate the ED correlation in Romania between 2002 and 2015. The methodology used: three unifactorial regression models showing how ED impacts economic indicators such as GDP, power purchase expressed through the net annual average salary, and household final consumption expenditure. Moreover, each model has been tested and verified using statistic tests to give reliable results. In a first stage, we analyzed the correlation between GDP and consumption as endogen variable and ED, then we created another model that we kept ED as an independent variable, but we changed the dependent variable using the purchasing power as a dependent variable. Because according to the used tests we demonstrated that correlation coefficients are significant, we proceeded to explain them starting from fiscal policy and economic reality, own of these analyzed 14 years. In conclusion we highlighted below as the ED depends on GDP and consumption and the purchasing power can influence the ED. For future discussion and studies we intend to compare the results with other countries in different geographic areas in Europe.